PEMETAAN LAHAN KRITIS UNTUK PENYEDIAAN LAHAN PERUMAHAN DI KABUPATEN BUTON TENGAH - Mitha Asyita Rahmawaty (Universitas Halu Oleo, 2020)
This study aims to 1) Determine the distribution of critical land in Central Buton Regency; 2) Analyze the location of critical land suitable for housing land supply in Central Buton Regency. The research location is in the Central Buton Regency, Southeast Sulawesi Province with an analysis unit per district. Data analysis techniques in this study used a map overlay with weighting based on the criteria for determining critical land. Besides that, an analysis technique is carried out the form of map buffering using road parameters to determine the suitable location of housing. Based on the Classification of Land Criticality in Central Buton District, land classification is Critical,Rather Critical and Potentially Critical is chosen as suitable land for housing land. Critical land classification with Very Critical level is almost in the whole area of Central Buton Regency. Almost all sub-districts in Central Buton District have Critical Land that is suitable for housing land except Talaga Raya District. Subdistricts with critical land for the largest housing land supply in Central Buton Regency are in Mawasangka District with an area of 235,672.81 M2 and Central Mawasangka District with an area of 214,179.80 M2Keywords: Central Buton Regency, Critical Land, Housing